Crisis counselling : caring for people in emotional shock - Stone, Howard W (London, SPCK, 1995)
Combining the traditional skills of pastoral counselling with more recent methods of crisis intervention from the fields of psychology and psychotherapy, Howard Stone provides guidance on all aspects of crisis counselling. He covers telephone counselling, suicide, bereavement, and more.
Keywords: Christianity.-- Pastoral work.-- Counselling; Pastoral Counselling; Crisis intervention (Mental health services)